Synthesis and formulation of functional bionanomaterials with superoxide dismutase activity. Issue 1 (7th December 2016) - Pavlovic, Marko; Rouster, Paul; Szilagyi, Istvan
Abstract : Stable dispersions of bionanocomposites with excellent superoxide radical scavenging ability were developed by immobilizing SOD on LDH coated with heparin. Abstract : Layered double hydroxide (LDH) nanoparticles were prepared and used as solid support for superoxide dismutase (SOD) enzymes. Structural features were studied by XRD, spectroscopic methods (IR, UV-Vis and fluorescence) and TEM, while colloidal stability of the obtained materials was investigated by electrophoresis and light scattering in aqueous dispersions. The SOD quantitatively adsorbed on the LDH by electrostatic and hydrophobic interactions and kept its structural integrity upon immobilization. The composite material showed moderate resistance against salt-induced aggregation in dispersions, therefore, heparin polyelectrolyte was used to improve the colloidal stability of the system. Heparin of highly negative line charge density strongly adsorbed on the oppositely charged hybrid particles leading to charge neutralization and overcharging at appropriate polyelectrolyte loading. Full coverage of the composite platelets with heparin resulted in highly stable dispersions, which contained only primary particles even at elevated ionic strengths. Our results indicate that the developed bionanocomposite of considerable enzymatic function is a suitable candidate for applications, wherever stable dispersions of antioxidant activity are required for instance in biomedical treatments or in chemical manufacturing processes.